2021
DOI: 10.35808/ijeba/660
|View full text |Cite
|
Sign up to set email alerts
|

Issues on Bank’s Capital Structure and Profitability: A Developing Country Context

Abstract: Purpose: The study aims to show the effect of capital structure on banks' profitability in developing countries. Design/Methodology/Approach: The study is conducted on 28 commercial banks from 2009 to 2016 of panel data to infer the concurrent relationship between capital structure and profitability. The preliminary diagnoses picked up the Generalized Methods of Moments (GMM) method to address the endogeneity issue in dynamic panel data. Findings: The study found that the bank's capital structure is negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…Statistical results reveals that there is a negative insignificant relationship that exists between listed banks' capital structure and their profitability (r=-68.6%, p-value=0.910). These findings were consistent with other studies (Lemmon & Zender, 2010: Niluthpaul & Roushanara, 2021) [19,24] , but contradicted a study by (Sivalingam & Kengatharan, 2018) [32] that discovered that a negative and significant relationship between profit an total debt of 28 commercial banks in Sri Lanka. Finally, these findings contradicted a study conducted by (Alipour et al, 2013) [2] , which concluded that profitability and capital structure have a positive relationship.…”
Section: Profitability and Total Debtsupporting
confidence: 88%
See 1 more Smart Citation
“…Statistical results reveals that there is a negative insignificant relationship that exists between listed banks' capital structure and their profitability (r=-68.6%, p-value=0.910). These findings were consistent with other studies (Lemmon & Zender, 2010: Niluthpaul & Roushanara, 2021) [19,24] , but contradicted a study by (Sivalingam & Kengatharan, 2018) [32] that discovered that a negative and significant relationship between profit an total debt of 28 commercial banks in Sri Lanka. Finally, these findings contradicted a study conducted by (Alipour et al, 2013) [2] , which concluded that profitability and capital structure have a positive relationship.…”
Section: Profitability and Total Debtsupporting
confidence: 88%
“…In another study that was conducted on 28 commercial banks from 2009 to 2016 to investigate the relationship between capital structure and profitability revealed that bank's capital structure negatively associated to profitability. (Niluthpaul & Roushanara, 2021) [24] . This study adopted the following hypothesis.…”
Section: Bank Profitmentioning
confidence: 98%
“…It indicates that leverage has a positive impact on return on equity. This finding is contradicts to the findings of Sarker and Islam (2021). Similarly, the beta coefficients for liquidity ratio are positive with return on equity.…”
Section: Tablecontrasting
confidence: 86%
“…Karim et al (2022) revealed that leverage ratios are negatively related to profitability and market return. Similarly, Sarker and Islam (2021) found that bank's capital structure is negatively associated with profitability and vice versa.…”
Section: Leveragementioning
confidence: 93%
“…Additionally, it showed that loan to asset ratios had a favorable and significant impact on ROA and ROE. Using panel data from 2009 to 2016, Sarker and Islam (2021) conducted a study, and the results showed a negative correlation between capital structure profitability. The profitability of the banks and their expansion were positively correlated.…”
Section: Introductionmentioning
confidence: 99%